ChemInform Abstract: Gold‐Catalyzed Tandem Diels—Alder Reactions of Enynals/Enynones with Alkenes: Generation and Trapping of Cyclic o‐QDMs. Issue 47 (6th November 2014) - Zhu, Shifa; Hu, Lang; Jiang, Huanfeng
Abstract The reaction proceeds through the trapping of cyclic o‐quinodimethane (cyclic‐o‐QDM) with electron‐deficient dienophiles [e.g. (III)] to afford unstable cyclohexene‐1, 4‐diones, which can be oxidized into the 1, 4‐benzoquinone on silica gel.